Dasyspora (Pucciniales) on Xylopia in the Amazon, with new distribution records for Brazil - Gomes, Gardênia Figueiredo; Sotão, Helen Maria Pontes; de Almeida, Layse Barreto; de França, Isadora Fernandes; Monteiro, Josiane Santana (Phytotaxa, 2025)
This work presents a taxonomic study with a morphological basis of Dasyspora (Sphaerophragmiaceae, Pucciniales) specimens deposited in herbaria of the Brazilian Amazon, aiming to update the status of this genus according to the recognition of the valid species complex. Specimens from the authors’ collections and from the collections of fungi and plants of the herbaria of Emílio Goeldi Museum of Pará (MG) and EMBRAPA Amazônia Oriental (IAN) previously identified as D. gregaria on Xylopia spp. were analyzed. Additional samples from other areas were also analyzed. Descriptions, images of nomenclatural types, and literature data complemented the identification and description of species. Six Dasyspora species were recorded in the Amazon (D. amazonica, D. echinata, D. ferrugineae, D. gregaria, D. nitidae and D. segregaria). New records are presented for Brazil (D. ferrugineae, D. nitidae and D. segregaria), and for the states of Amapá (D. echinata), Mato Grosso (D. amazonica), Pará (D. amazonica and D. echinata) and Rondônia (D. gregaria and D. segregaria). The additional samples studied were D. segregaria from Peru and D. ferrugineae from Surinam. Characteristics and the distribution of ornamentations on the wall of the teliospores were the main morphological attributes that differentiate the species. Host specificity was observed at the host genus level, but not at the host species level. The new records expand the geographic distribution of rust fungi in Brazil. Descriptions, illustrations, taxonomic comments, geographic distribution of fungi and host plants, and an identification key for known species in South America are presented.